Computed tomography imaging of acute gastrointestinal graft-versus-host disease after haematopoietic stem cell transplantation in children - Arpaci, Taner (TERMEDIA PUBLISHING HOUSE LTD, 2018)
Aim of the study: To evaluate computed tomography (CT) findings of gastrointestinal graft-versus-host disease (GI-GVHD) occurring in children after haematopoietic stem-cell transplantation (HSCT). Material and methods: From February 2013 to May 2018, 225 paediatric patients underwent HSCT. Sixty-eight patients (30\%) presented with clinical diagnosis of acute GI-GVHD in the first 100 days after HSCT. Thirty-five (18 girls, 17 boys

age range, 2-18 years

mean age, 10.3 years) of 68 patients had abdominopelvic CT and included in study. Results: Intestinal CT abnormalities were present in 33 (94\%) and extra-intestinal CT findings were in 30 (86\%) patients. Thickening of the bowel wall was the most common finding (31 patients, 89\%), which involved the small bowel in 29 patients (83\%), colon in 16 patients (46\%), and both in 15 patients (43\%). Oesophageal wall thickening was present in three patients (9\%), and gastric wall thickening was in eight patients (23\%). Bowel dilatation was detected in 13 patients (37\%). Mucosal enhancement of the bowel wall was observed in 28 patients (80\%). The prevalence of the extra-intestinal CT findings were: periportal oedema in nine (26\%), ascites in 15 (43\%), wall thickening and enhancement of gall bladder in 13 (37\%), pericholecystic fluid in six (17\%), hepatomegaly in 13 (37\%), and splenomegaly in nine (26\%) patients. One patient (3\%) demonstrated free intraperitoneal air due to intestinal perforation. Conclusions: CT is useful to support the clinical diagnosis of acute GVHD in children with GI symptoms after HSCT. Radiological evaluation is important because early diagnosis and treatment affect the prognosis of GI-GVHD.
Keywords: computed tomography; gastrointestinal system; graft-versus-host disease; haematopoietic stem cell transplantation